PERANCANGAN DAN PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN ADOBE ANIMATE PADA MATA PELAJARAN SENI TARI SISWA KELAS XI DI SMKN 7 PADANG TAHUN AJARAN 2025/2026 - Azaro, Salsabilla; Wijaya, Indra; Jafnihirda, Lika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to design and develop interactive learning media using Adobe Animate for the Dance subject for Grade XI students at SMKN 7 Padang and to determine the feasibility of the developed media in terms of validity, practicality, and effectiveness. The interactive learning media were developed to enhance students' interest and learning outcomes through interactive, engaging, and user-friendly learning materials. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 33 Grade XI students at SMKN 7 Padang. Data were collected using validity questionnaires, practicality questionnaires, and effectiveness tests. The results of the validity test conducted by experts showed a percentage of 94.33%, which was categorized as very valid. The practicality test conducted by students obtained a percentage of 89.93%, which was categorized as very practical, while the effectiveness test yielded a percentage of 89.7%, which was categorized as very effective. Based on these findings, it can be concluded that the interactive learning media developed using Adobe Animate met the criteria of being very valid, very practical, and very effective, making it suitable for use as a learning medium in the Dance subject for Grade XI students at SMKN 7 Padang.